1997
DOI: 10.1021/jm9703045
|View full text |Cite
|
Sign up to set email alerts
|

2-Carbomethoxy-3-aryl-8-oxabicyclo[3.2.1]octanes:  Potent Non-Nitrogen Inhibitors of Monoamine Transporters

Abstract: Cocaine is a potent stimulant of the mammalian central nervous system. Its reinforcing and stimulant properties have been associated with its propensity to bind to monoamine transporter systems. It has generally been assumed that the amino function on monoamines is a requirement for binding to monoamine transporters. In particular, the 8-amino function on the tropane skeleton of cocaine and cocaine analogs has been assumed to provide an ionic bond to the aspartic acid residue on the dopamine transporter (DAT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
106
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 50 publications
9
106
2
Order By: Relevance
“…It has long been thought that the nitrogen atom is needed for amine-containing drugs to bind to the biological target, 5 but Madras and colleagues have recently shown that the nitrogen atom may be replaced by either an oxygen atom 6,7 or a carbon atom (BK Madras et al, to be published), and the cocaine-like drugs will still selectively block the dopamine transporter target in vitro. (Although the nitrogen and oxygen atoms each have lone pair electrons which can form a hydrogen bond with the dopamine transporter, 5,7 the carbon atom does not, thus raising considerably interesting theoretical problems as to how such carbon-based molecules bind to the dopamine transporter.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been thought that the nitrogen atom is needed for amine-containing drugs to bind to the biological target, 5 but Madras and colleagues have recently shown that the nitrogen atom may be replaced by either an oxygen atom 6,7 or a carbon atom (BK Madras et al, to be published), and the cocaine-like drugs will still selectively block the dopamine transporter target in vitro. (Although the nitrogen and oxygen atoms each have lone pair electrons which can form a hydrogen bond with the dopamine transporter, 5,7 the carbon atom does not, thus raising considerably interesting theoretical problems as to how such carbon-based molecules bind to the dopamine transporter.…”
Section: Chemistrymentioning
confidence: 99%
“…Thus, amphetamine has two forms, (+)-and (−)-, while methylphenidate has two asymmetric carbon atoms, resulting in four forms, wherein the mixed form (±)-threo-methylphenidate is used clinically. Although each stimulant contains a nitrogen atom which can bond to the dopamine transporter target, Madras and colleagues have shown that the nitrogen atom can be replaced by an oxygen atom 6,7 or a carbon atom (Madras et al, to be published) while still retaining the drug's potency in vitro.…”
Section: Behavioral Pharmacologymentioning
confidence: 99%
“…Similarly modified methylphenidate analogs displayed DAT affinities indistinguishable from methylphenidate itself (Meltzer et al, 2003). In contrast, replacement of the basic tropane nitrogen with a neutral functional group (e.g., N-formyl group or oxygen atom) in the benztropine class of DAT inhibitors substantially reduced DAT binding affinity (Agoston et al, 1997;Meltzer et al, 1997;Simoni et al, 2001).…”
mentioning
confidence: 98%
“…On the other hand, a similar 8-oxa modification of WIN 35,428 sharply reduced binding affinity and DUIP at the DAT. This deficit was fully compensated for by further replacing the p-fluoro substituent of the C-3 phenyl group with a chloride atom (Madras et al, 1996) and further improved with a 3,4-dichloro substitution (Meltzer et al, 1997). Elimination of hydrogen bonding potential at the 8-position of WIN 35,428 by substitution of a carbon atom also substantially compromised affinity at the DAT.…”
mentioning
confidence: 99%
“…Overlap of high affinity inhibitor binding with the S1 site is supported by biochemical studies (38,44,47,55) and by recent structures of Drosophila (d) DAT and a LeuT/SERT hybrid co-crystallized with antidepressants (40,56). However, some DA transport inhibitors lack the charged nitrogen necessary to form the salt bridge with Asp-79 (57)(58)(59), suggesting that inhibitor binding can occur without this interaction and thus may not be limited to the S1 pocket (60). This possibility is supported by crystal structures of LeuT complexed at relatively low affinity with several selective serotonin uptake inhibitors (SSRIs) and tricyclic antidepressants (TCAs) in regions that overlap with S2 (16 -18, 56).…”
mentioning
confidence: 99%